A Multi-agent System in E-Health SystemImplementing EBDI model - Abir Hussein jabber, Prof. Ali Obied, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Agent technology has seen tremendous expansion in recent years in various disciplines, particularly in the domain of E-health. where The discipline of medicine is distinguished by its complexity, dynamism, and variety. Different challenges occur in healthcare (increasing cost of care, population growth, and lack of caregivers). so the features of Intelligent Agents (proactivity, intelligence, sociability, and autonomy)are a suitable choice to solve many challenges in this domain because the major success criteria were the natural translation of realworld medical concerns into electronic life. also, these characteristics result in lower operating costs and the automated execution of activities in various Agent-based systems, As a result, intelligent applications based on Agent Technology may be able to deliver better health care than the traditional medical system. In reality, One of the most intriguing aspects of contemporary health care is the prospect of automating basic activities such as monitoring patients' conditions and giving quick assistance in emergency circumstances. The implementation of multi-agent systems (mas) in the healthcare field has also paved the way for new applications such as socialized and customized healthcare models. As a result, this paper attempts to create a multiagent system as well as an agent-based system for the hospital. and this article explains how the use of EBDI-based software agents and jade framework can help to automate various processes while also improving patient service.